Dinamika Geopolitik Global dalam Era Multipolar: Tantangan dan Peluang Bagi Indonesia - Maharani, Reva Rezalita (Maliki Interdisciplinary Journal, 2025)
This study analyzes the dynamics of global geopolitics in a multipolar era and its implications for Indonesia’s strategic position. The multipolar era is characterized by the emergence of new powers such as China, India, and Russia, challenging U.S. hegemony. Employing a qualitative approach, this research analyzes secondary data from journals, books, and official reports. Findings indicate that Indonesia faces challenges such as tensions in the South China Sea and global trade competition, but also has opportunities to enhance its role in ASEAN diplomacy and economic cooperation with developing nations. Specifically, economic diversification and technological capacity building are critical to seizing these opportunities. The study underscores the need for adaptive foreign policy and investment in human resources to boost Indonesia’s global competitiveness.